1972
DOI: 10.1021/jf60182a042
|View full text |Cite
|
Sign up to set email alerts
|

.alpha.-Trichloromethylbenzylanilines and .alpha.-trichloromethylbenzyl phenyl ethers with DDT-like insecticidal action

Abstract: A series of p,p'-disubstituted a-trichloromethylbenzylanilines which closely resemble DDT-type compounds in structure have been synthesized and evaluated for insecticidal activity. These compounds affect insects in a manner indistinguishable from DDT, and the most effective compounds such as a-trichloromethyl-p-ethoxybenzyl-p-methylaniline were of comparable toxicity with DDT to flies and mosquito larvae. The metabolism of W-a-trichloromethyl-p-ethoxybenzyl-p-ethoxyaniline was studied in the housefly, salt-mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The following 14C-labeled pesticides were obtained: aldrin, ring-labeled, 68.0 mCi/mmole (Amersham Searle), dieldrin, ring-labeled, 1.03 mCi/ mmole (Shell Chemical); endrin, ring-labeled, 2.3 mCi/mmole (mallinkrodt); mirex, ringlabeled, 1.74 mCi/mmole (Mallinkrodt); lindane, ring-labeled, 54 mCi/mmole (Amersham Searle); hexachlorobenzene, ringlabeled, 4.61 mCi/mmole (National Institute of Environmental Health Sciences); DDT, ring-labeled, 5.48 mCi/mmole (Amersham Searle). DDT was converted to DDE (2,2-bisp-chlorophenyl-1,1-dichloroethylene), 5.48 mCi/mmole, by treatment with ethanolic potassium hydroxide and purification by column chromatography. Several of the radiolabeled pesticides contained impurities visible after TLC and autoradiography, and these products were repurified by column chromatography through silicic acid with petroleum ether (60-68°C) as the eluent until they were at least 99+% radiochemically pure.…”
Section: Expeimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The following 14C-labeled pesticides were obtained: aldrin, ring-labeled, 68.0 mCi/mmole (Amersham Searle), dieldrin, ring-labeled, 1.03 mCi/ mmole (Shell Chemical); endrin, ring-labeled, 2.3 mCi/mmole (mallinkrodt); mirex, ringlabeled, 1.74 mCi/mmole (Mallinkrodt); lindane, ring-labeled, 54 mCi/mmole (Amersham Searle); hexachlorobenzene, ringlabeled, 4.61 mCi/mmole (National Institute of Environmental Health Sciences); DDT, ring-labeled, 5.48 mCi/mmole (Amersham Searle). DDT was converted to DDE (2,2-bisp-chlorophenyl-1,1-dichloroethylene), 5.48 mCi/mmole, by treatment with ethanolic potassium hydroxide and purification by column chromatography. Several of the radiolabeled pesticides contained impurities visible after TLC and autoradiography, and these products were repurified by column chromatography through silicic acid with petroleum ether (60-68°C) as the eluent until they were at least 99+% radiochemically pure.…”
Section: Expeimental Proceduresmentioning
confidence: 99%
“…The problem is both controversial and momentous, as 88,641,000 pounds of cyclodienes and toxaphene and 59,316,000 pounds of DDT were produced in the United States in 1970 (1). The laboratory model ecosystem devised in this laboratory (2) has been used to estimate the comparative environmental properties of DDT, methoxychlor, and other DDT analogs (3)(4)(5). These investigations have demonstrated environmental degradative pathways and have provided quantitative data on ecological magnification and biodegradability index (6).…”
mentioning
confidence: 99%
“…This indicates that it could degrade photochemically in the environment. Degradation of a diethoxy analog of 1 in a model ecosystem gave several products including those corresponding to 4, 5, and 6 (Hirwe et al, 1972). A further unknown was pres-…”
Section: Discussionmentioning
confidence: 99%
“…In this way each molecule would have a propensity for self-destruction in sunlight, regardless of its chemical environment. Fortunately, Hirwe et al (1972) recently synthesized a series of compounds with attributes desirable for our goal. One of these was A/-(a-trichloromethyl-p-methoxybenzyl)-p-methoxyaniline (1).…”
mentioning
confidence: 99%
“…[212][213][214][215][216][217] Scheme 34. [236][237][238][239][240][241][242][243] Recently, Wahl et al 244 reported a nucleophilic addition of trimethyl(trichloromethyl)silane (108) to N-phosphinoyl benzaldimines 107 outlining a tetrabutylammonium difluorotriphenylsilicate (TBAT)-catalyzed route to N-phosphinoyl-α-(trichloromethyl)benzylamines 109 in tetrhydrofuran (THF) with good yields within just one hour at room temperature (Scheme 38). The resulting β-hydroxy nitro compounds have been used in various beneficial transformations to provide chiral β -amino alcohols and α-hydroxy carboxylic acids.…”
Section: Addition Reactionsmentioning
confidence: 99%